48/80 MADDESİNİN PROKONVÜLSAN ETKİSİ VE MORFİN İLE ETKİLEŞİMİ - YILLAR, D. Okan; AKCASU, Alaeddin; SILAN, Coşkun (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Some compound 48/80 administered mice respond to voiced and tactile stimulation by a convulsion-like contraction and this effect is decreased by morphine. After these two observations; it was thought that compound 48/ 80 passes somehow to the central nervous system. For this reason, we aimed to determine the effect of these two substances on maximal electroshock seizure (MES). (1) In the first part of study, convulsive current 50 (CCSO) was determined as 46 mA. In all electroshocks this level was used during whole study. (2) 5 mg/kg compound 48/80 was administered subcutanously (s.c.) to mice and electroshock was given in different time intervals (15, 30, 60, 120, 240 min). (3) Mice's mast cells were depleted and electroshock was administered to both groups (control and 5 mg/kg 48/80 given group) at the 60th minute. (4) In this part of the study the MES response of control and morphine administered group (100 mg/kg) was determined at the 30th and Goth minutes. (5) In the last section, electroshock was given to morphine and compound 48/80 administered mice groups. Results.- (1) Convulsive current (CCSO) was 46 mA. (2) Compound 48/80 decreased the maximal electroshock seizure threshold at the 60th minute significantly (p<0.0001). (3) It also decreased MES threshold in mast cell depleted mices. (4) When morphine and compound 48/80 were administered, anticonvulsant effect of morphine was increased. (5) Death mice is changed in every step of our study by an unknown mechanism. Conclusion.- Compound 48/80 decreased maximal electroshock seizure threshold by an unknown mechanism. Combination of morphine and compound 48/80 increased the anticonvulsant effect of morphine. This effect probably raised from the ability of compound 48/80 to increase the permeability of blood-brain barrier.